Avaliação da atitude do estudante de medicina a respeito da relação médico-paciente na Universidade José do Rosário Vellano de Belo Horizonte - PAIVA, M. P. (2018)
Introduction: Medical schools, in general, have a curriculum focused on the biomedical aspects that favor the development of an authoritarian and disease-focused attitude at the end of the course. Studies have evaluated the student's attitude towards curricular changes that transform the clinical method. Objectives: Evaluate the attitude of medical students towards the patient: whether they show attitudes centered on the person or the illness and demonstrate tendencies of sharing of power and care, in a school that adopts the methodology of learning based on problems (PBL), after introducing the teaching of the person-centered clinical method in the skills training strategy. Methods: Student attitude was assessed using the EOMP scale, which measures individual preferences in aspects of the physician-patient relationship. The EOMP provides three types of scores: the total EOMP score (ETOT), a subscale that evaluates the ability to share decisions, power subscale (SEP), and another that assesses how much the professional believes that feelings, emotions and problems of the patient's personal life should be considered in the care planning process, the subscale of care (SEC). Participants were 1st, 3rd, 5th, 7th, 9th and 11th semester students of the 1st semester of 2017. The mean scores were compared using ANOVA. Results: The mean scores of EOMP for the whole sample of respondents were: ETOT of 4.53 (± 0.46), SEC 4.92 (± 0.46) and SEP 4.15 (± 0.67). ANOVA showed that there is no interaction between the student's period and the EOMP scores in relation to the doctor-patient relationship, however, there is a significant influence between gender and the course period and gender factors in the measurement of the scores. It was observed that the mean of the EOMP scores at the end of the course was higher among the male students in relation to the female gender. The analysis of conglomerates showed that there is a significant association between the scores and the fact that the student has a scholarship. The results resemble a previous study conducted at this school in 2008. Conclusion: The instructional changes in the teaching of the person-centered clinical method did not modify the pattern of evolution of PMPO. It is worth noting the gain in the EOMP score in male students, from the beginning to the end of the course, attributed fact, in the first study to the PBL methodology.